Repercussion of Price and Promotion on Consumer Interest at CV. XYZ Business in Surabaya - Achmad Daengs GS; Enny Istanti; I Gede Wiyasa (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to examine the influence of price and promotion on consumer interest at CV. XYZ in its embroidery business activities. The current problem faced is that CV. XYZ, as a provider of embroidery art services, is not well known among individual or corporate customers. Meanwhile, competitors in the same industry aggressively carry out promotions and advertisements through print media such as newspaper inserts, tabloids, and electronic media. This has greatly impacted the lack of consumer interest in using embroidery services, leading to a decline in CV. XYZ sales volume and its inability to compete with competitors.A quantitative approach was used in this study. Primary data was obtained from 35 respondents. The research shows that there is a significant partial influence of the price and promotion variables on consumer interest at CV. XYZ in the embroidery business. This is demonstrated by the t-test results using SPSS software, where the t-value for Price is 31.988, which is greater than the t-table value of 2.03011, and the t-value for Promotion is 38.815.Simultaneously, it was found that Price and Promotion variables together influence Consumer Interest at CV. XYZ in the embroidery business, with an F-value of 3252.406, which is greater than the F-table value of 2.5. The R value is 0.998 and the simultaneous determination coefficient (R square) is 0.995, meaning that 99.5% of the variation in consumer interest is influenced by Price and Promotion, while the remaining 0.5% is influenced by other variables not studied.Furthermore, this test shows that Price is the most dominant variable influencing consumer interest, as evidenced by the standardized regression coefficient (β) of 0.515, which is higher than the coefficient values for other variables.